BALI CULTURE EXPLORATION IN DEVELOPMENT OF FRIENDLY SCIENCE TEACHING MATERIALS FOR HEARING AND SPEAKING IMPAIRMENT STUDENTS AT INCLUSION SCHOOL - Gede Parma, Putu; Ira Pratiwi, Desak Komang; Bayu, Gede Wira (JPI (Jurnal Pendidikan Indonesia), 2020)
Bengkala Village is a village where 2% or around 48 people are born with hearing and speaking impairment. They still have an artistic spirit by forming a kolok janger group. To support the development of education, in 2007, the local government established SDN 2 Bengkala as an inclusive school. At present, this school does not yet have specific teaching material in learning science that is deaf-friendly. This study aimed to explore Balinese culture in development of friendly teaching materials in inclusive schools using development research methods. In this study, exploration was carried out by students using the ADDIE model. The instruments used to measure the quality of teaching materials were an assessment sheet of teaching materials from experts for the validity aspects, learning achievement tests, as well as teacher response questionnaires and student response questionnaires to assess teaching materials applied. Validity analysis was done with the formula of content validity ratio according to Lawshe and the effectiveness test analysis was done through quantitative descriptive analysis. The results of this study are some products in the form of teaching materials for Natural Sciences which are equipped with RPP/lesson plan and LKPD/worksheets with the development of insightful Balinese culture. This products have been validated by natural science experts, learning design experts, Balinese cultural experts, as well as evaluation and education experts. The results obtained with a CVR and CVI score was 1.00 which can be categorized as "valid" and worth testing. These products have been tested limited in fourth grade. Conclusions of this study were the product can improve learning outcomes of hearing and speaking impairment in inclusive schools.